Forensic engineering : informing the future with lessons from the past : proceedings of the fifth International Conference on Forensic Engineering - Carpenter, John (Institution of Civil Engineers Publishing, 2013)
This book is the published proceedings from the Institution of Civil Engineers' Fifth International Conference on Forensic Engineering, held in London on 16-17 April 2013. The papers in this book focus on the investigation of the fundamental causes of failure during the life of buildings, tunnels, bridges and foundations, which is crucial for optimising the construction and management of the built environment to deliver a better and more sustainable infrastructure. With more than 40 contributors, spread across 16 countries and six continents, this is an essential text, providing valuable lessons for owners, managers, developers and all those seeking to learn from the past to best manage their assets. --